2012
DOI: 10.1080/13504851.2011.591726
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of Italian public debt: alternative paths for fiscal consolidation

Abstract: This article analyses possible targets for the Italian debt-to-GDP ratio with a small macroeconomic model. The role of international macroeconomic variables such as the US GDP growth, prices of raw materials, EUR/USD exchange rate and European Central Bank (ECB) monetary policy stance and domestic policy instruments is analysed in the debt dynamics. We find that external conditions play a fundamental role for the Italian fiscal consolidation. To reach a target of 100% of debt-to-GDP ratio by 2020, a further gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…Dalena and Magazzino (2012) showed that public expenditure and revenues are cointegrated in each selected sub-period (Magazzino 2012). Casadio et al (2012) showed that a policy intervention aimed to stimulate the GDP growth over 1.8% allows to reach the target 100% debt-to-GDP ratio. The empirical evidence by Piergallini and Postigliola (2012) shows the occurrence of a significantly positive reaction of primary surpluses to debt when the debt/GDP ratio exceeded the trigger value of 110%.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Dalena and Magazzino (2012) showed that public expenditure and revenues are cointegrated in each selected sub-period (Magazzino 2012). Casadio et al (2012) showed that a policy intervention aimed to stimulate the GDP growth over 1.8% allows to reach the target 100% debt-to-GDP ratio. The empirical evidence by Piergallini and Postigliola (2012) shows the occurrence of a significantly positive reaction of primary surpluses to debt when the debt/GDP ratio exceeded the trigger value of 110%.…”
Section: Empirical Literaturementioning
confidence: 99%
“…There is a positive however very small effect on inflation. Also investigating the role of macroeconomic variables including US GDP growth, the price of oil, EUR/USD exchange rate, European Central Bank monetary policy stance and domestic policy instruments on the Italian debt-to-GDP ratio, Casadio et al (2012) argue that external conditions play an important role in Italian fiscal consolidation. In contrast to the VAR methodology employed by most studies, they employ the seemingly unrelated regression (SUR) estimation method.…”
Section: The Literaturementioning
confidence: 99%
“…We follow the approach of Favero and Marcellino (2005), Hasko (2007), and Casadio et al (2012) in specifying a small macroeconomic model for Greece. We start off with the evolution of public debt::…”
Section: A Macroeconomic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According their estimates, a significant and sustainable reduction of debt/GDP ratio can be achieved over the next years if policymakers raise (up to 0.30) fiscal pressure's elasticity to public debt evolution, and/or reduce primary government expenditure by four percentage points over the next 4 years. Based on the simple arithmetic of public finance, they performed a number of simulation regarding the evolution of public finance aggregates Casadio et al (2012). analyzed possible targets for the Italian debt-to-GDP ratio with a small macroeconomic model.…”
mentioning
confidence: 99%